Analysis of the Money Demand Function in MENA Countries: The Role of Macroeconomic Variables - Saeed Hawi, Hameedah; Karimi Takanlou, Zahra; Salmani Bishak, Mohammad Reza; Aleemran, Seyed Ali (Digital Transformation and Administration Innovation, 2025)
This study investigates the factors affecting money demand in selected MENA countries including Iraq, Iran, Qatar, the United Arab Emirates, Saudi Arabia, Algeria, Turkey, Morocco, and Egypt from 1993 to 2023 using the CS-ARDL model. Cross-sectional dependence and heterogeneity of slope coefficients were examined to provide the initial conditions of the model. The results confirmed both of them. Westerlund test also showed the existence of a long-run relationship (cointegration) between variables in some countries and the entire panel. The final model examined the effect of variables such as oil revenues, government expenditures, inflation, exchange rate, domestic interest rate, and foreign interest rate on money demand. The results revealed that oil revenues have a positive and significant effect in the short and long run, while government expenditure has no effect. Inflation and domestic and foreign interest rates have a negative and significant effect, and the exchange rate has a positive and significant effect on money demand in both periods. The negative and significant adjustment coefficient (67.4 percent) indicates a rapid return to long-run equilibrium. The unit root test also confirmed the persistence of the residuals, indicating the validity of the long-run relationship between the variables I (0) and I (1). The results can be used to formulate coordinated monetary and fiscal policies, especially in countries dependent on oil revenues.